POSITIVE POLITENESS STRATEGIES USED BY DAVID MUIR AND DONALD TRUMP ON “ABC NEWS” AND IN “CHARLIE ROSE SHOW” - Kharis Marpudianto (Department of Master of Linguistic, Universitas Airlangga, 2020)
Abstract This research examines Donald Trump and David Muir’s Utterances on ABC News and in Charlie Rose Show. The researcher also focuses positive politeness used by David Muir and Donald Trump. The researcher mainly utilized Pragmatics theory by Brown and Levinson which consists of four strategies, there are positive politeness, negative politeness, bald on record, and off record but, the researcher only focuses in positive politeness. As the methodology, the researcher used descriptive-qualitative approach to concern the description and the interpretation of Donald Trump videos. Under descriptive-qualitative method, this research significantly gives a wider understanding about how linguistic subjects emerges through pragmatics structure. The researcher gathered the data by downloading the interviews of Donald Trump on ABC News and in Charlie Rose Show, also the factors that influenced positive politeness used by David Muir and Donald Trump. As the result, there are 28 data were collected in this research and contained 10 types of positive politeness strategies based on Brown and Levinson’s theory. Moreover, there are two factors that influenced David Muir and Donald Trump. Those are social distance and relative power. Keywords: Pragmatics, Politeness Strategy, Positive Politeness, Donald trump, David Muir.Abstrakpenelitian ini meneliti ucapan Donald Trump dan David Muir di ABC News dan Charlie Rose Show. Peneliti juga memfokuskan pada strategi kesantunan positif yang digunakan oleh David Muir dan Donald Trump. Peneliti menggunakan teori pragmatik dari Brown and Levinson yang terdiri dari empat strategi yaitu, kesantunan positif, kesantunan negatif, ujaran secara langsung, ujaran secara tidak langsung. Tetapi, peneliti hanya lebih fokus di strategi kesantunan positif. Peneliti menggunakan metode deskriptif kualitatif yang berhubungan dengan deskripsi dan interpretasi dari video Donald Trump. Dengan menggunakan metode deskriptif kualitatif bisa memberikan pengertian lebih luas tentang pelajaran linguistik dengan melalui teori pragmatik. Peneliti memperolah data dengan mengunduh video wawancara Donald Trump di ABC News dan Charlie Rose Show dan ada dua faktor yang mempengaruhi David Muir dan Donald Trump. Sebagai hasil dari penelitian ini, peneliti menemukan 28 data yang terdapat di penelitian ini dan ada 10 macam srategi kesantunan positif. Selain itu ada 2 sebab yang mempengaruhi David Muir dan Donald Trump untuk melakukan strategi kesopanan positif yaitu jarak sosial dan kekuasaan tidak mutlak. Kata kunci: Pragmatik, Strategi Kesantunan, Kesantunan Positif, Donald Trump, David Muir.